Examining the motivators affecting acceptance towards learning management systems for sustainable learning amid COVID-19 pandemic - Lai, Chung Yee; Cheung, Kwok Yip; Pang, Li Li Lily (Frontiers in Education, 2024)
This study explores the motivators to use learning management systems (LMS) adopted and used in eLearning by Hong Kong universities among Mainland Chinese postgraduate students amid COVID-19 pandemic. An adapted and extended UTUAT2 model was first proposed and tested using the structural equation modeling approach. Through self-report online questionnaire, data were collected in 2022 from 352 Mainland Chinese postgraduate students of nine universities in Hong Kong. The reliability and validity of the data were tested using the confirmatory factor analysis, followed by path analysis to test the hypotheses in the proposed model. The study revealed nine motivators which explained 50% of the variance in LMS use intention. Trust (0.204), instructor characteristics (0.202), performance expectancy (0.181), and facilitating conditions (0.181) were identified as strong motivators of behavioral intention. Other factors such as effort expectancy (0.148), learning value (0.118) and social influence (0.115) also had significant positive effects on LMS use intention. Habit (0.014) and hedonic motivation (-0.016) had no significant direct effect on it. These findings provide inspirations for educational stakeholders to promote the acceptance of LMS platforms among distance and online learners who adopt the cyberspace as the only means of learning. They also offer insights about instructor recruitment and evaluation methods.